Victimization of employees to students: explicit violence, disguised by school practices and neglect (Research, Society and Development, 2020)
It is not known what is the scope of victimization of employees to students and the factors that influence this phenomenon, since there are few studies about it and the instruments for investigating the problem. This study aimed to evaluate the psychometric characteristics of the Student Employee Victimization Scale (Evaf). To this end, the responses to the research instrument of 1,484 public school students from the 6th to the 9th grade of elementary school from six cities in four Brazilian states were analyzed. It was noted that the scale is formed by three factors: explicit violence; disguised by school practices; and neglect, which together explain 57.9% of the variance, with an internal consistency index of 0.85. Thus, Evaf presented two theoretically adequate dimensions, addressing items representative of the phenomenon of victimization of employees to students, with moderate internal consistency. In conclusion, Evaf proved to be a favorable instrument for this type of research.